PENGARUH TAYANGAN SINETRON GANTENG-GANTENG SERIGALA TERHADAP CITRA SCTV DIKALANGAN MAHASISWA FISIP ILMU KOMUNIKASI UNTAG SURABAYA - Sari, Muthia Ayu Kartika; Sudaryanto, Edy; Yulianti, Tri (representamen, 2016)
Handsome-handsome Wolf is a soap opera that aired ditelevisi teenage drama theprivate SCTV, which aims to provide entertainment for the community particularly theadolescents-the adolescentsAuthors interested in taking the title "influence Impressionssoap opera Handsome-handsome Wolves Against the image of SCTV communicationstudies and POLITICAL SCIENCE Student Among Untag Surabaya." The variables usedin this research is variable telenovela handsome-handsome Wolf (variable X) with twoindicators measuring levels of audience attention, namely against soap opera ganteng –ganteng serigala and the measurement of audience acceptance level against soap operahandsome-handsome Wolf. And image among students FROM SCTV communicationsciences Untag Surabaya (variable Y) with 4 indicator that is based on the 4 componentsof perception, cognition, motivation and attitude. Analysis of the results obtained from theconclusion that the research results are significant, which results from the calculation ofSPSS Output it can be concluded that the correlation between variables X and Yvariables have values that can be found on the 0.571 had a strong correlation, and basedon the test results showed significance values 0.000 which means the Association of thesetwo variables is significant.Keyword :Telenovela ganteng – ganteng serigala, Image SCTV